Clinical Application of a Cardiac Diagnostic Method Based on Dynamic Systems Theory (2017)
A new methodology based on dynamical systems theory has been developed to differentiate normal cardiac dynamic from acute illness by calculating the space occupation of chaotic geometric attractors in the phase space. Objective: The purpose of this study was to apply this methodology to confirm its clinical applicability and the relation between the measures and the appearance of arrhythmic electrical storms.